2014
DOI: 10.1021/jp5068236
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Kinetic Performance of Water Desorption for N2 Adsorption in Li-LSX Zeolite

Abstract: The effect of small amounts of water in inhibiting the adsorption of N2 gas on different cationic forms of LSX zeolite was investigated using thermogravimetric and derivative thermogravimetry (TG-DTG) techniques at different heating rates, which is shown to be a very effective way of studying the influence of strongly adsorbed water on adsorption of less-strongly adsorbed N2 molecules. According to DTG profiles, the apparent activation energies (E) relating to the thermal desorption of water molecules existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 47 publications
3
17
0
Order By: Relevance
“…In bi-metallic Ag x Li 96-x -LSX zeolites a significant amount of most tenaciously held (chemisorbed and crystalline) water removed at higher temperatures (620-780 K) as compared to parent Li x Na 96-x -LSX (620-800 K) zeolite and is found in good agreement with our previously reported results and literature. 29 Furthermore, as it has also been reported in our previous studies that sodalite-cage and double six-ring (hexagonal prism) are sterically inaccessible to nitrogen molecules, therefore initial physisorption of water is not expected to influence the nitrogen adsorption, whereas chemisorbed water largely occupies SIII sites in α-cages (supercages) strongly influence the adsorption capacity 16 capacity after dehydration at 573 K and this decrease in N 2 adsorption capacity cannot only be attributed to the low content of crystalline water but also to the formation of charged silver clusters in zeolite at high temperature. Therefore complete suppression of N 2 and O 2 adsorption on bi-metallic Ag x Li 96-x -LSX zeolites by presorbed water molecules might be an evident cause of molecular sieving effect caused by the blocking of twelve ring windows of supercages.…”
Section: Characterizationsmentioning
confidence: 75%
See 4 more Smart Citations
“…In bi-metallic Ag x Li 96-x -LSX zeolites a significant amount of most tenaciously held (chemisorbed and crystalline) water removed at higher temperatures (620-780 K) as compared to parent Li x Na 96-x -LSX (620-800 K) zeolite and is found in good agreement with our previously reported results and literature. 29 Furthermore, as it has also been reported in our previous studies that sodalite-cage and double six-ring (hexagonal prism) are sterically inaccessible to nitrogen molecules, therefore initial physisorption of water is not expected to influence the nitrogen adsorption, whereas chemisorbed water largely occupies SIII sites in α-cages (supercages) strongly influence the adsorption capacity 16 capacity after dehydration at 573 K and this decrease in N 2 adsorption capacity cannot only be attributed to the low content of crystalline water but also to the formation of charged silver clusters in zeolite at high temperature. Therefore complete suppression of N 2 and O 2 adsorption on bi-metallic Ag x Li 96-x -LSX zeolites by presorbed water molecules might be an evident cause of molecular sieving effect caused by the blocking of twelve ring windows of supercages.…”
Section: Characterizationsmentioning
confidence: 75%
“…26 SEM image of Ag 3.87 Li 88.82 Na 3.31 -LSX is shown in Fig. 1B 16 While the SEM results of Ag x Li 96-x -LSX also confirmed that the crystallite morphology after silver exchange were remained intact and sizes varied between 5.35-6.8 µm as shown in Fig. 1B (inset), were found in agreement with the XRD results and further confirmed that no major changes were occurred in the structure.…”
Section: Characterizationsmentioning
confidence: 99%
See 3 more Smart Citations